In vitro reminiscence: uterine programming in vivo affects respective luminal epithelial cells function in vitro† - Rocha, Cecilia Constantino; Cordeiro, Andrey Luiz Lopes; Campbell, Meghan; Maldonado, Mariangela Bueno Cordeiro [UNESP]; Carvalho Silva, Felipe Alves Correa; Bennett, Alexandra; Waheed, Abdul; Hansen, Thomas; Binelli, Mario (Oxford University Press (OUP), 2024)
In cattle, the endometrium during diestrus and early pregnancy displays cellular responses that are consequences of prior, transient stimuli. Goal was to establish a model to study cellular memory in the endometrium. The hypothesis is that stimuli given to endometrium in vivo are retained as a cellular memory that remains after bovine uterine epithelial cells (BUECs) are isolated, cultured, and further stimulated in vitro. Objectives were to measure BUEC proliferation/migration and responsiveness to recombinant bovine Interferon-tau (rbIFNT) in vitro: among cows that showed estrus (experiment 1 [Exp1]), cows that became or not pregnant to artificial insemination (Exp2), cows that received or not supplemental progesterone (P4; Exp3) and cows that received or not a COX-1/2 inhibitor (Exp4). Only cows that displayed estrus were included in studies. For all experiments endometrial cytology was collected 4 days after estrus, BUECs were cultured, propagated, and submitted to rbIFNT treatment and an in vitro scratch assay. In Exp1, different cows spontaneously grouped according to proliferative/migratory capacity and responsiveness to rbIFNT of their respective BUECs. In Exp2, BUECs from pregnant cows showed greater rbIFNT responsiveness and cellular proliferation. In Exp3, BUECs from cows supplemented with P4 presented inhibited proliferation and increased expression of RSAD2. In Exp4, Flunixin Meglumine modified rbIFNT responsiveness of BUECs in an IFN-signaling pathway-specific manner. In conclusion, physiological and pharmacological stimuli received by the endometrium in vivo were retained as cellular memory in BUECs, persisted in culture, and changed BUEC proliferation/migration and responsiveness to rbIFNT, which are characteristics associated with fertility in cattle.
Keywords: cellular memory; estrus; in vitro scratch assay; interferon-tau; luminal epithelial endometrial cells; migration; pre-implantation; pregnancy; proliferation